Evaluasi Pelaksanaan Proyek Drainase Dengan Metode CPM Dan PERT - Gunaedy Utomo; Irna Hendriyani; Siti Nor Aida (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
This research purposes to evaluate the implementation of the drainage project in Jl. Mulawarman, Gg. Arjuna, Sepinggan. This research uses the CPM (Critical Path Method) and the PERT (Project Evaluation and Review Technique). Based on the budget plan, time schedule, weekly report, documentation and interview found that the result of the CPM with two critical paths are work activities. The first critical path are: Activity A (Mobilization and Demobilization), Activity C (Landfilling activity), Activity F (Concrete works K-175, Ready Mix). The second critical path are: Activity A (Mobilization and Demobilization), Activity E (Begisting work for black channels), and Activity G (Plain U24 Concrete Iron Works). Meanwhile, the result of PERT has 49% chance to be completed with the project duration of 18 weeks.